Active distribution network fault section location method based on characteristic wave coupling - Zhiren Liu; Kai Chen; Jinghua Xie; Xiaolong Wu; Wenzhou Lu (IET Renewable Power Generation)
Abstract As distributed generators (DG) and power electronic devices become more integrated, distribution networks have evolved from being passive to active, and power flow has shifted from unidirectional to bidirectional. This transformation has negatively impacted power quality, leading to weakened fault transient attributes and increased harmonic complexities. Consequently, the efficacy of traditional relay protection has diminished, elevating the risk of misoperation or misjudgment and compromising the safety of distribution networks. In response to these challenges, a fault section location method for active distribution network based on characteristic wave coupling is proposed to expand the fault difference. This method explores the principles of characteristic wave coupling, discusses characteristic wave parameter selection theory, examines the start‐up control strategy for characteristic wave coupling, and establishes a protection action criterion by comparing the energy difference of characteristic waves based on the fault identification principle. Subsequently, by utilizing multiple inverter interfaced distributed generators to actively couple characteristic waves into the distribution network during faults, achieves rapid identification and location of fault sections. Finally, the effectiveness of the method is substantiated through simulation results in MATLAB/Simulink and experimental outcomes obtained from a low‐voltage active distribution network experimental platform based on dSPACE1103.